THE IMPACT OF ESG DISCLOSURE AND CSR ON FIRM VALUE IN INDONESIA'S FMCG SECTOR - Rini Sulistiyowati; Silfiana Indri Oktofia; Efa Wahyuni (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
This study aims to examine the influence of Environmental, Social, and Governance (ESG) Disclosure and Corporate Social Responsibility (CSR) on Firm Value in the Fast-Moving Consumer Goods (FMCG) sector in Indonesia. The main objective of this study is to determine whether non-financial disclosures such as ESG and CSR can affect firm value in the FMCG sector listed on the Indonesia Stock Exchange. This study uses a quantitative approach with a panel data research design, which applies the Pooled OLS, Fixed Effects, and Random Effects regression models. The research sample consists of 28 FMCG companies listed on the Indonesia Stock Exchange in the period 2021–2024. The data used are sourced from annual reports and company sustainability reports. Data analysis techniques include panel data regression, the Chow Test, the Hausman Test, and the Lagrange Multiplier Test for appropriate model selection. The results of the t and F tests are used to examine the partial and simultaneous effects of variables on Firm Value. The results show that although the regression model is significant, ESG Disclosure and CSR do not have a significant effect on Firm Value. This research provides theoretical and practical contributions in understanding the relationship between non-financial disclosure and firm value